Through the moon / Through the Moon - Wartman, Peter; Bouna, Xanthe (New York, NY : Graphix, an imprint of Scholastic, 2020)
Rayla, Callum, and Ezran are summoned by an ancient ritual to a portal between life and death, where Rayla's search to confirm Lord Viren's death is complicated by unexpected dangers.
At head of title: The dragon prince, an original graphic novel.
Chiefly illustrations.
Keywords: Adventure and adventurers -- Fiction; Fantasy; Graphic novels; Graphic novels